2011
DOI: 10.1186/1472-6963-11-140
|View full text |Cite
|
Sign up to set email alerts
|

Communication, advice exchange and job satisfaction of nursing staff: a social network analyses of 35 long-term care units

Abstract: BackgroundThe behaviour of individuals is affected by the social networks in which they are embedded. Networks are also important for the diffusion of information and the influence of employees in organisations. Yet, at the moment little is known about the social networks of nursing staff in healthcare settings. This is the first study that investigates informal communication and advice networks of nursing staff in long-term care. We examine the structure of the networks, how they are related to the size of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Nurses working in units with a close communication network are more satisfied with their work. In units with few employees, nurses are more likely to be satisfied with their work compared with units with many employees (van Beek et al, 2011). The quality of both communication and advice networks was negatively related to the number of nursing staff on units.…”
Section: Interprofessional Communication In Health Carementioning
confidence: 93%
See 2 more Smart Citations
“…Nurses working in units with a close communication network are more satisfied with their work. In units with few employees, nurses are more likely to be satisfied with their work compared with units with many employees (van Beek et al, 2011). The quality of both communication and advice networks was negatively related to the number of nursing staff on units.…”
Section: Interprofessional Communication In Health Carementioning
confidence: 93%
“…This social network is important for the dissemination of information. Social networks are advantageous for people's career and job performance (van Beek et al, 2011;Wagner et al, 2015).…”
Section: Interprofessional Communication In Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Given the Ethiopian healthcare delivery context is very hierarchical the existence of informal advice networks is a noteworthy nding. Similarly, a study of Dutch nurses in a long-term care facility found advice networks to be non-hierarchical, although they only looked within one cadre [54]. In studies of inter-professional communication hierarchy is common [7,34,[55][56][57][58].That said, the reliance on informal advice networks may be a product of infrequent supportive supervision visits and review meetings Advice exchange varied by cadre, but universally there was more advice exchanging between cadres than within cadres.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of line implies the number of co-occurrence frequency of these herbs. The numbers of lines indicate the density of the relationship among these herbs, and the tense areas indicate more communications and strong cohesion of the network on the unit [34,[62][63][64][65][66][67]. As shown, the connection among gardenia jasminoides ellis, rhizoma corydalis, Panax ginseng, ligusticum, Fructus aurantii immaturus, Glycyrrhiza uralensis, Ophiopogon japonicus, Cassia twig and Bupleurum Chinense, etc.…”
Section: Social Network Analysis Of Single Herbs Included In Traditiomentioning
confidence: 97%